Holocene East Asian Summer Monsoon Rainfall Variability in Taiwan - Ding, Xiaodong; Zheng, Liwei; Zheng, Xufeng; Kao, Shuh-Ji (Frontiers in Earth Science, 2020)
Characterizing the spatiotemporal variability of the East Asian summer monsoon (EASM) advances our understanding of its rhythm, dynamics, and future impacts. EASM variations during the Holocene have been reconstructed from a variety of geological archives and proxies. However, the spatiotemporal heterogeneity of EASM rainfall during the Holocene remains controversial. Taiwan is geographically suitable for studying the EASM history through its geological archives. Herein, we synthesize the reported lake and peat sedimentary records of the entire Holocene, in addition to the records of mass-wasting and on-land deposition from cores collected from Taiwan to illustrate the EASM induced hydroclimate changes in Taiwan throughout the Holocene. Records from Taiwan indicate that the EASM rainfall maximum occurred during the early Holocene, concurring with other EASM records from monsoon region of southern China. We suggest that the early Holocene EASM rainfall maximum in southern China was mainly forced by the higher Northern Hemisphere summer insolation and sea surface temperatures in the Western Pacific Warm Pool (WPWP). A synthesis of EASM rainfall records from across China shows that the timing of Holocene EASM rainfall maximum occurred progressively later from southern to northern China. This time-transgressive EASM rainfall maximum may be due to the latitudinal shift of the westerlies and Western Pacific subtropical high (WPSH) that induced by changes of interhemispheric temperature gradients (ΔTN‐S) and northern high latitude ice volume. Moreover, records from Taiwan suggest a significant collapse of the EASM in Taiwan at ~4–2 ka BP. Based on the records from Taiwan, coastal East Asian and Tropical Pacific, we propose that the sea surface temperatures (SSTs) of the WPWP and/or El Niño -Southern Oscillation (ENSO) activity may have exerted a strong influence on the EASM rainfall changes during the late Holocene. Moreover, increased EASM rainfall in southern China during the last 2 ka was likely caused by a southward shift of WPSH which was associated with gradual decreases in ΔTN‐S during the late Holocene.